Hematology of the Red-Capped Parrot (Pionopsitta pileata) and Vinaceous Amazon Parrot (Amazona vinacea) in Captivity - dos Santos Schmidt, Elizabeth Moreira [UNESP]; Lange, Rogerio Ribas; Ribas, Janaciara Moreira; Daciuk, Barbara Maria; Montiani-Ferreira, Fabiano; Paulillo, Antonio Carlos [UNESP] (Amer Assoc Zoo Veterinarians, 2009)
Preliminary reference intervals for hematologic and total plasma protein profiles were determined for nine adult Red-capped parrots (Pionopsitta pileata) (six males and three females) and six Vinaceous Amazon parrots (Amazona vinacea) (two adult males, two adult females, one juvenile. and one nonsexed) from the Curitiba Zoo, Parana. Brazil. For both Red-capped parrots and Vinaceous Amazon parrots. adult males had higher red blood cell counts than adult females. Regarding white blood cell distribution, differences due to gender were also found for both species of parrots.
Keywords: Avian hematology; Pionopsitta pileata; Amazona vinacea; Red-capped parrot; Vinaceous Amazon parrot; Psittacidae